Lissencephaly-1 dependent axonal retrograde transport of L1-type CAM Neuroglian in the adult drosophila central nervous system. - Kudumala, S.R.; Penserga, T.; Börner, J.; Slipchuk, O.; Kakad, P.; Lee, L.H.; Qureshi, A.; Pielage, J.; Godenschwege, T.A. (PLoS ONE, 2017)
Here, we established the Drosophila Giant Fiber neurons (GF) as a novel model to study axonal trafficking of L1-type Cell Adhesion Molecules (CAM) Neuroglian (Nrg) in the adult CNS using live imaging. L1-type CAMs are well known for their importance in nervous system development and we previously demonstrated a role for Nrg in GF synapse formation. However, in the adult they have also been implicated in synaptic plasticity and regeneration. In addition, to its canonical role in organizing cytoskeletal elements at the plasma membrane, vertebrate L1CAM has also been shown to regulate transcription indirectly as well as directly via its import to the nucleus. Here, we intend to determine if the sole L1CAM homolog Nrg is retrogradley transported and thus has the potential to relay signals from the synapse to the soma. Live imaging of c-terminally tagged Nrg in the GF revealed that there are at least two populations of retrograde vesicles that differ in speed, and either move with consistent or varying velocity. To determine if endogenous Nrg is retrogradely transported, we inhibited two key regulators, Lissencephaly-1 (Lis1) and Dynactin, of the retrograde motor protein Dynein. Similar to previously described phenotypes for expression of poisonous subunits of Dynactin, we found that developmental knock down of Lis1 disrupted GF synaptic terminal growth and that Nrg vesicles accumulated inside the stunted terminals in both mutant backgrounds. Moreover, post mitotic Lis1 knock down in mature GFs by either RNAi or Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) induced mutations, resulted in normal length terminals with fully functional GF synapses which also exhibited severe accumulation of endogenous Nrg vesicles. Thus, our data suggests that accumulation of Nrg vesicles is due to failure of retrograde transport rather than a failure of terminal development. Together with the finding that post mitotic knock down of Lis1 also disrupted retrograde transport of tagged Nrg vesicles in GF axons, it demonstrates that endogenous Nrg protein is transported from the synapse to the soma in the adult central nervous system in a Lis1-dependent manner.